The world of art. The currency of kantian concept of autonomy of art - Carrillo Castillo, Lucy (Estudios de Filosofía, 2000)
The Kantian thought strength arises from its understanding —and defending— the enigma of the work of art considered an achieved conciliation of genius and taste, of nature and spirit. Due to that autonomy, the work of art, though an intentional human product, is not born only to fulfill practical, cognitive or emotional needs; though it appears as one more thing among things, it does not simply adds to the world but transforms it. Summarizing this property of the work of art, Kant talks about its ability to provoke aesthetic ideas, thanks to which the intuition of imagination can provide the thought with interesting contents, without being forced to prefix them or define them in advance.